O Pioneers! - Cather, Willa (Prairie Trilogy., 2015)
Willa Cather's powerful story about a family of farmers--an instant American classic The first novel in Willa Cather's Prairie Trilogy tells the story of the Bergsons, a family of immigrants eking out a hardscrabble life as farmers in Nebraska at the turn of the nineteenth century. Alexandra, the eldest child of Bergson patriarch John, inherits the family farm when her father dies. Left to raise her father's three sons and somehow turn a struggling farm around, Alexandra is tasked with pulling her family up by its bootstraps. Unfortunately, her brothers aren't made of the same strong pioneer stock as she is. When drought, depression, and other agricultural disasters hit, it's up to Alexandra to pull the family through. Along the way, the neighbor boy, Carl Linstrum, catches her eye. But when families begin lighting out for greener pastures in the West, the Bergsons' fortunes take a turn. Can the family survive the brutal Midwest hardships, or worse--the Bergson brothers' frivolous nature? Will Alexandra, emotional lodestone and embodiment of the American can-do spirit, ever find happiness--or love? Cather's novel shows readers the story of the American frontier. O Pioneers! is the 1st book in the Prairie Trilogy, but you may enjoy reading the series in any order. This ebook has been professionally proofread to ensure accuracy and readability on all devices.